2013
DOI: 10.1155/2013/690491
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of Umbilical Cord Mesenchymal Stem Cells in Mice Premature Ovarian Failure

Abstract: Mesenchymal stem cells, which are poorly immunogenic and have potent immunosuppressive activities, have emerged as promising cellular therapeutics for the treatment of several diseases. Mesenchymal-like cells derived from Wharton's Jelly, called umbilical cord matrix stem cells (UCMSCs), reportedly secrete a variety of cytokines and growth factors, acting as trophic suppliers. Here, we used UCMSCs to treat premature ovarian failure (POF). Ovarian function was evaluated by ovulation and the number of follicles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 44 publications
6
97
1
1
Order By: Relevance
“…hUCMSCs were prepared, identified, and cultured according to a recently published protocol (23). At passage 6, the expression of cell surface markers was analyzed with flow cytometry using fluorescein isothiocyanate (FITC)-conjugated human monoclonal antibodies such as CD14 (BioLegend, 325623), CD31 (BioLegend, 303103), CD34 (BioLegend, 343603), CD105 (BioLegend, 323203), CD45 (BioLegend, 304005), CD44 (BioLegend, 338803), CD73 (BioLegend, 344015), human leukocyte antigens-D region (HLA-DR, BioLegend, 307603), phycoerythrin (PE)-conjugated human antibodies against CD90 (BioLegend, 328109), and PE-CD29 (BioLegend, 303003).…”
Section: Preparation Culture and Identification Of Hucmscsmentioning
confidence: 99%
See 1 more Smart Citation
“…hUCMSCs were prepared, identified, and cultured according to a recently published protocol (23). At passage 6, the expression of cell surface markers was analyzed with flow cytometry using fluorescein isothiocyanate (FITC)-conjugated human monoclonal antibodies such as CD14 (BioLegend, 325623), CD31 (BioLegend, 303103), CD34 (BioLegend, 343603), CD105 (BioLegend, 323203), CD45 (BioLegend, 304005), CD44 (BioLegend, 338803), CD73 (BioLegend, 344015), human leukocyte antigens-D region (HLA-DR, BioLegend, 307603), phycoerythrin (PE)-conjugated human antibodies against CD90 (BioLegend, 328109), and PE-CD29 (BioLegend, 303003).…”
Section: Preparation Culture and Identification Of Hucmscsmentioning
confidence: 99%
“…Evidence has shown that hUCMSCs have unique advantages compared to BMSCs (22), which make them a promising source of cells for treatment. According to previous studies, stem cells to treat ovarian injury are primarily administered via intravenous injection (IV) or in situ ovarian micro injection (MI) (23)(24)(25)(26). However, very few studies have examined suitable forms of hUCMSC therapy to delay ovarian aging.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been shown in animal models that MSCs from different sources (e.g. adipose) can improve or even restore ovarian function [56][57][58][59]. To determine the ideal age at which POMSCs could be used to regenerate ovaries, the ovarian tissue of more patients at different ages would need to be included.…”
Section: Discussionmentioning
confidence: 99%
“…Few other groups have transplanted mesenchymal cells in chemoablated ovary and reported restored ovarian function. [72][73][74][75][76] All these groups have transplanted cells immediately after chemotherapy and have not waited for chemotherapy to completely destroy follicular reserve. Hence the effect appears more protective than restoration of ovarian function.…”
Section: Differentiation Potential Of Vsels That Survive Chemotherapymentioning
confidence: 99%